No free lunches: PES and the funding of agricultural biodiversity conservation insights from a competitive tender for quinoa-related conservation services in Bolivia and Peru - Drucker, Adam; Padulosi, Stefano; Jager, Matthias (Bioversity International, 2020)
Mechanisms are explored through which agrobiodiversity service beneficiaries and purchasers could become investors in its conservation and sustainable use. Such mechanisms include eco-labelling, biodiversity offsets and other regulatory obligations, public procurement programmes, corporate social responsibility initiatives and the development of cultural tourism infrastructure, as well as direct support from government and institutions. An examination is undertaken of the required enabling environment to support these investments, which potentially include changes in government policy to facilitate/encourage private sector involvement, the development of PACS-related institutions for monitoring, verification and enforcement, as well as donor and consumer awareness-raising and dialogue.